Analysis of Tariff Calculation, Payment and Reporting of Value Added Tax (VAT) (Case Study of PT. GoTo Gojek Tokopedia TBK Listed on the Indonesia Stock Exchange for the 2021-2022 Period) - Sari, Indah Puspita; Rahmaniar, Ani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Value-added tax. On April 1 2022, the government officially increased the single tax rate for Value Added Tax (VAT) by 1% from previously 10% to 11%. Tax reporting made by the company is fully in accordance with applicable laws and regulations, in other words sales are maintained well. The purpose of this research is to determine the analysis of calculating, depositing and reporting value added tax (VAT) (case study PT. Goto Gojek Tokopedia Tbk). The method used in this research is descriptive quantitative, with the calculation object including details of input VAT and details of output VAT, depositing and reporting value added tax to the company. The data used in the research uses secondary data sourced from the BEI website (www.idx.com). PT. GoTo Gojek Tokopedia Tbk 2021-2022 to find out VAT calculations, deposits and reporting. The results of this research indicate that PT GoTo Gojek Tokopedia Tbk has carried out calculations, deposits and reporting of value added tax in accordance with tax standards and applicable laws and regulations.